ilia_mahan

5 Reputation

One Badge

9 years, 117 days

MaplePrimes Activity


These are questions asked by ilia_mahan

hello
i have a problem that you could help me
i have an expression that i want convert it to an expression according to the expression q[d] with maple
i have bellow expressions
B[d]:=(-d*w[1]+w[3])/(((-2*w[1]+w[3])^2)-((-d*w[1]+w[3])^2))
B[o]:=(-2*w[1]+w[3])/(((-2*w[1]+w[3])^2)-((-d*w[1]+w[3])^2))
A[o]:=w[1]*(alpha[o]-c[o]-t[o])+2*w[2]*e[o]
A[d]:=w[1]*(alpha[d]-c[d]-t[d])+2*w[2]*e[d]
q[o]:=B[o]*A[o]-B[d]*A[d]
q[d]:=B[o]*A[d]-B[d]*A[o]
i want simplify expression U[d] such as this one
U[d]:=w[1]*(q[d]*(alpha[d]-q[d]-d*q[o]-c[d]-t[d])-C)+w[2]*(e[d]*q[d]+e[o]*q[o])+w[3]*((1/2)*(q[d]+q[o])^2)
I'm looking to simplify U[d] according to the expression q[d]
please please help me

Page 1 of 1